One page talent management eliminating complexity, adding value - Effron, Marc; Ort, Miriam (Ascent Audio, 2025)
"You know that winning in today's marketplace requires top-quality talent. You also know what it takes to build that talent. Yet somehow, your company's beautifully designed and well-benchmarked processes don't translate into the bottom-line talent depth you need. Why? Talent management experts Marc Effron and Miriam Ort argue that companies unwittingly add layers of complexity to their talent-building models. Consequently, simple activities like setting employee performance goals become multi-page, headache-inducing time wasters that turn managers off and fail to improve results. Effron and Ort introduce a simple, powerful, scientifically proven approach to increase your ability to develop better leaders faster: One Page Talent Management (OPTM). Using the straightforward, easy-to-follow process described in this book, you will eliminate frustrating complexity, focus only on those components that add real value, and build transparency and accountability into every practice. One Page Talent Management shows you how to quickly identify high-potential talent without complex assessments; increase the number of ""ready now"" successors for key roles; generate 360-degree feedback that accelerates change in the most critical behaviors; and significantly reduce the time required for managers to implement talent-building processes. ".
Online resource; title from title details screen (O'Reilly, viewed April 15, 2025)
Keywords: Manpower planning; Human capital -- Management; Performance; Personnel management; Performance technology; Main-d'uvre; Planification; Personnel; Direction; Audiobooks; Livres audio